Framework for opportunistic routing in wireless sensor networks with application to multiple antennas in fading environments - Hamilton, Benjamin R; Gidlund, Mikael; Culver, Stephen (Melecon 2010 - 2010 15th IEEE Mediterranean Electrotechnical Conference, 2010)
In this article we present a framework for routing based on a distributed routing decision and adapt the framework on a multiple-input multiple-output (MIMO) system. Our proposed framework provides a cross-layer design where the routing decision is decided through silent negotiation between candidate relays. The proposed protocol divides the routing decision between transmitter and the receivers: the transmitter decides the direction and an angle spread to broadcast the packet; each receiver, without communicating each other, decides whether to start a timer whose duration depends on the strength of the channel state information. The node with the shortest timer transmits first and thus becomes the transmitter for the next hop. We verify the performance of the proposed framework by computer simulations.